CULTURAL TOURISM: FRENCH ATTRACTIONS - Lysa Gautier; Aline Poinclou; Estelle De Carvalho; Marie Cazaban Loustaunau (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2018)
This is an article about some famous tourist attractions in France according to the academic subject “cultural tourism”. It is a subject which is a point of interest for us because it is part of a patrimony and culture. It seems that it can be useful for Indonesian people to know a little bit of a French culture. It is hoped it will give the desire to come and visit France. In order to write this article, we first used our personal knowledge of those tourist attractions that we have already visited several times for some of them. To complete those information and adjust some details, we read some press articles and use each tourist attraction official websites. In this article, we will present four famous tourist attractions: two in Paris, one in Normandy and one in Bordeaux. They are The Château Pape Clément, The Mont Saint Michel, The Eiffel Tower, and the Palace of Versailles.